Fine mapping and candidate gene analysis of CRA8.1.6, which confers clubroot resistance in turnip (Brassica rapa ssp. rapa) - Wei, Xiaochun; Xiao, Shixiong; Zhao, Yanyan; Zhang, Luyue; Nath, Ujjal Kumar; Yang, Shuangjuan; Su, Henan; Zhang, Wenjing; Wang, Zhiyong; Tian, Baoming; Wei, Fang; Yuan, Yuxiang; et al. (Frontiers in Plant Science, 2024)
Clubroot disease poses a significant threat to Brassica crops, necessitating ongoing updates on resistance gene sources. In F2 segregants of the clubroot-resistant inbred line BrT18-6-4-3 and susceptible DH line Y510, the genetic analysis identified a single dominant gene responsible for clubroot resistance. Through bulk segregant sequencing analysis and kompetitive allele-specific polymerase chain reaction assays, CRA8.1.6 was mapped within a 110 kb (12,365 Mb) between markers L-CR11 and L-CR12 on chromosome A08. We identified BraA08g015220.3.5C as the candidate gene of CRA8.1.6. Upon comparison with the sequence of disease-resistant material BrT18-6-4-3, we found 249 single nucleotide polymorphisms, seven insertions, six deletions, and a long terminal repeat (LTR) retrotransposon (5310 bp) at 909 bp of the first intron. However, the LTR retrotransposon was absent in the coding sequence of the susceptible DH line Y510. Given the presence of a non-functional LTR insertion in other materials, it showed that the LTR insertion might not be associated with susceptibility. Sequence alignment analysis revealed that the fourth exon of the susceptible line harbored two deletions and an insertion, resulting in a frameshift mutation at 8551 bp, which leading to translation termination at the leucine-rich repeat domain's C-terminal in susceptible material. Sequence alignment of the CDS revealed a 99.4% similarity to Crr1a, which indicate that CRA8.1.6 is likely an allele of the Crr1a gene. Two functional markers, CRA08-InDel and CRA08-KASP1, have been developed for marker-assisted selection in CR turnip 2 cultivars. Our findings could facilitate the development of clubroot-resistance turnip cultivars through marker-assisted selection.